Design And Construction Service Tunnels On Palm Jumeirah Island - Michael Ryjevski; Ben Hayes (Society for Mining, Metallurgy & Exploration, 2007)
The Palm Jumeirah is the smallest of the three Palm Islands (Palm Jumeirah, Palm Jebel Ali and Palm Deira). It is located on the Jumeirah coastal area of the emirate of Dubai, in the United Arab Emirates (UAE). The unique man made island is built in the shape of a date palm tree and consists of a trunk, a crown, 17 fronds and a surrounding crescent island that will form a breakwater. The Jumeirah Palm Island is primarily are treat and residential area for living, relaxation, and leisure. It will contain themed boutique hotels, three types of villas, shoreline apartment buildings, beaches, marinas, restaurants, cafes and a variety of retail outlets.